Computational Studies on Reactions of Some Organic Azides with C−H Bonds. Issue 17 (5th May 2021) - Devi, Shougaijam Premila; Mittal, Ankit; Kakkar, Rita
Abstract: The computational methods, B3LYP and MP2 with the basis set 6‐311++G(d, p) have been used to decipher the energetics and mechanisms of different nitrene reactions, namely organic azide decomposition, singlet and triplet nitrene addition to different kinds of C−H bonds, azide insertion into C−H bonds and substitution reaction of azides to alkanes. The addition of singlet nitrene to the C−H bond is exothermic, with one‐step addition accompanied by a considerable barrier, where the sequence of facility H>Ac>Me indicates the electrophilic nature of the nitrene reactant. In the case of triplet nitrene, the initial step involves smaller barriers and is endothermic due to the formation of radicals as intermediate products, and the final step involves the coupling of radicals and is hence exothermic. The direct azide addition has higher barrier then the stepwise addition reaction. The Hammond postulate can be used to differentiate the transition state geometries for different reaction steps as "early" or "late". Abstract : Azides either gets decomposed to nitrenes before adding to the C−H bond or added directly to the C−H bond, forming the corresponding products. This works deals with the mechanistic study of the insertion reactions of different organic azides to the C−H bond of alkane substrates. Out of three plausible pathways, two (decomposition of azide and substitution reaction of azide) are endothermic, but one (direct addition of azide to alkane) is exothermic.